La inversión pública y su incidencia en el crecimiento económico del Ecuador periodo 2000 - 2013. - Guevara Tello, Stalin Mario (2016)
: The present investigation titled "The public investment and their incidence in the economic growth in the Ecuador period 2000 - 2013", It has as objective to analyze the influence that has the public investment as independent variable on the dependent variable the economic growth. Where all the information and gathered evidence is shown in charts, graphics and analysis that allow knowing the behavior of these variables during the study period The chapter I, In the Framework explains how it originates the position of the problem, the formulation of the problem, the general and specific objectives. In this chapter it is shown the justification and importance of this investigation and the objectives that later on will be completed. In the chapter II, Theoretical Marco, it contains the concepts, limits and the legal mark of the Public Investment in the Ecuador, as well as the focuses of the fiscal politics that the state manages with the purpose of influencing in the Economic Growth, the theoretical foundation of the two variables is shown with the purpose of explaining in an adapted way each one of these. In the chapter III the methodological Framework, includes all the methodology used for the investigation of the variables, this chapter evolutionary analysis of all-time series that includes the model shown, as well as analysis of participation and influence of the independent variable with respect to economic growth. This under the requirements of a Vector Autoregressive model that have been processed with the views software. In the chapter IV includes conclusions were reached after the investigation process and also the author's recommendations with the purpose of generating some good results in the dependent variable, Economic Growth.